3D Printed Pressure Sensor Based on Surface Acoustic Wave Resonator - Hu, Baofa; Li, Zhiwei; Wan, Yuanjie; Zhou, Peng; Zhang, Chunquan; San, Haisheng (Measurement Science Review, 2021)
This paper reports a 3-dimentional (3D) pressure sensor based on surface acoustic wave (SAW) resonators. The SAW resonators were designed and fabricated on 128°Y-X LiNbO3 substrate using the MEMS technology. The pressure sensing structure was 3D-printed using polyactic acid plastic, and two SAW resonators were integrated in the 3D-printed chamber structure for both temperature and pressure sensing. The SAW-based gas pressure sensors demonstrate a sensitivity of 589 ppm/MPa at the pressure range of 100-600 kPa and temperature of 40 °C.